2019
DOI: 10.1162/jocn_a_01454
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional MRI Evidence for Distinct Medial Temporal and Prefrontal Roles in Context-dependent Relational Memory

Abstract: Declarative memory is supported by distributed brain networks in which the medial-temporal lobes (MTLs) and pFC serve as important hubs. Identifying the unique and shared contributions of these regions to successful memory performance is an active area of research, and a growing literature suggests that these structures often work together to support declarative memory. Here, we present data from a context-dependent relational memory task in which participants learned that individuals belonged in a single room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 137 publications
(213 reference statements)
1
20
2
Order By: Relevance
“…This work represents the first detailed investigation of the mechanical properties of parcellations of the cerebral cortex, though initial MRE investigations into cortical structure-function relationships Schwarb et al, 2019), contributions to adolescent risk-taking behavior (McIlvain et al, 2020), and the mechanical integrity of the cortex in Alzheimer's disease (Hiscox, Johnson, McGarry, Marshall, et al, 2020) This MRE study is the first to report significant sex differences in viscoelasticity in a wide range of neuroanatomical structures which supplements the wealth of existing data that reports sex differences in neuroanatomy. Interestingly, we found that female brains are approximately 4% more viscous compared to males as indicated by significantly higher ξ in global WM, which contradicts an early study that reported female brains were 9% less viscous in large regions primarily comprising white matter (Sack, Streitberger, Krefting, Paul, & Braun, 2011).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This work represents the first detailed investigation of the mechanical properties of parcellations of the cerebral cortex, though initial MRE investigations into cortical structure-function relationships Schwarb et al, 2019), contributions to adolescent risk-taking behavior (McIlvain et al, 2020), and the mechanical integrity of the cortex in Alzheimer's disease (Hiscox, Johnson, McGarry, Marshall, et al, 2020) This MRE study is the first to report significant sex differences in viscoelasticity in a wide range of neuroanatomical structures which supplements the wealth of existing data that reports sex differences in neuroanatomy. Interestingly, we found that female brains are approximately 4% more viscous compared to males as indicated by significantly higher ξ in global WM, which contradicts an early study that reported female brains were 9% less viscous in large regions primarily comprising white matter (Sack, Streitberger, Krefting, Paul, & Braun, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…This work represents the first detailed investigation of the mechanical properties of parcellations of the cerebral cortex, though initial MRE investigations into cortical structure–function relationships (Johnson et al, 2018; Schwarb et al, 2019), contributions to adolescent risk‐taking behavior (McIlvain et al, 2020), and the mechanical integrity of the cortex in Alzheimer's disease (Hiscox, Johnson, McGarry, Marshall, et al, 2020) have been reported. We show that separate regions of the cortex exhibit different viscoelastic properties and, remarkably in some cases, observe distinct viscoelastic properties which do not overlap in the range of values across participants.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations